Investigating the effects of muscle contraction and conditioning stimulus intensity on short‐interval intracortical inhibition. (18th July 2019) - Hendy, Ashlee M.; Ekblom, Maria M.; Latella, Christopher; Teo, Wei‐Peng
Abstract: A reduction in short‐interval intracortical inhibition (SICI) has been shown to accompany acute or chronic resistance exercise; however, little is known about how SICI is modulated under different contraction intensities. Therefore, the purpose of this study was to assess the effect of muscle contraction and conditioning stimulus intensity on the modulation of SICI. Single‐ and paired‐pulse transcranial magnetic stimulation was applied to the primary motor cortex (M1), and motor evoked potentials (MEPs) were recorded from the biceps brachii in 16 adults (10M/6F). A conditioning‐test stimulus paradigm (3 ms inter‐stimulus intervals) was delivered during 10%, 20%, 40% and 75% of maximal voluntary isometric contraction (MVIC). At each force level, conditioning stimulus intensities of 60%, 70% and 80% of active motor threshold (AMT) were tested. Single‐pulse MEPs were expressed as a proportion of the maximal muscle compound action potential, while SICI was quantified as a ratio of the unconditioned MEP. MEP amplitude increased with force output, with the greatest increase at 75% of MVIC. A reduction in SICI was observed from 40% to 75% of MVIC, but not 10%–40% of MVIC. There was no significant interaction between conditioning stimulus intensity and force level. The conditioning stimulus intensity (60%, 70% or 80% of AMT) did not alter the modulation of SICI. SICI was reduced at 75% of MVIC compared with the lower force outputs, and the magnitude of SICI in individual participants at different force outputs was not related. The findings suggest that strong muscle contractions are accompanied by less inhibition, which may have implications for neuroplasticity in exercise interventions. Abstract : We investigated the effect of conditioning stimulus intensity (60%, 70% and 80% of active motor threshold) and muscle contraction strength (10%, 20%, 40% and 75% of maximum) on short‐interval intracortical inhibition (SICI) in the biceps brachii. The results suggest that SICI is reduced (less inhibition) at higher levels of contraction but is not affected by the conditioning stimulus intensity.